Solar and geothermal energy - Tabak, John. (New York : Facts on File, 2009)
Describes a brief history of solar and geothermal energy, the way they are used and why they are two of the best sources of power for the environment.
pt. I: Solar energy. A brief history of solar power -- Sunlight and geometry -- Photovoltaics -- Heat engines and solar power -- Two other important solar technologies -- Economic and environmental consequences of solar power -- Government policies and solar energy -- pt. II: Geothermal energy. A brief history of geothermal energy -- Geology and heat -- The generating station -- Two other geothermal technologies -- The economics and environmental impacts of electricity from geothermal sources -- Government policies and geothermal energy -- Chronology -- List of acronyms -- Glossary.
Description based on print version record.
Includes bibliographical references (p. 188-192) and index.
Keywords: Renewable energy sources -- Juvenile literature; Electronic books